2019
DOI: 10.1128/mbio.00225-19
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Fibroblasts Drive Host Inflammatory Responses That Are Dependent on Chlamydia trachomatis Strain Type and Likely Influence Disease Outcomes

Abstract: Chlamydia trachomatisocular strains cause a blinding disease known as trachoma. These strains rarely cause urogenital infections and are not found in the upper genital tract or rectum. Urogenital strains are responsible for a self-limited conjunctivitis and the sequelae of infertility, ectopic pregnancy, and hemorrhagic proctitis. However, the differential cellular responses that drive these clinically observed disease outcomes are not completely understood. Primary conjunctival, endocervical, and endometrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 107 publications
4
11
0
Order By: Relevance
“…Infection with C. trachomatis involves a complex interplay between many cell-types that orchestrate cytokine and chemokine production to stimulate leukocyte, granulocyte, and monocyte production and homing to the infection site. Our study and recent published work (Jolly et al, 2019) suggest that stromal fibroblasts and genitourinary epithelial cells play an important role in the initial response to C. trachomatis. Importantly, we and others (Jolly et al, 2019) have shown that the innate immune response to C. trachomatis is mounted in a cell-type and serovar-specific manner.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Infection with C. trachomatis involves a complex interplay between many cell-types that orchestrate cytokine and chemokine production to stimulate leukocyte, granulocyte, and monocyte production and homing to the infection site. Our study and recent published work (Jolly et al, 2019) suggest that stromal fibroblasts and genitourinary epithelial cells play an important role in the initial response to C. trachomatis. Importantly, we and others (Jolly et al, 2019) have shown that the innate immune response to C. trachomatis is mounted in a cell-type and serovar-specific manner.…”
Section: Discussionsupporting
confidence: 74%
“…Our study and recent published work (Jolly et al, 2019) suggest that stromal fibroblasts and genitourinary epithelial cells play an important role in the initial response to C. trachomatis. Importantly, we and others (Jolly et al, 2019) have shown that the innate immune response to C. trachomatis is mounted in a cell-type and serovar-specific manner. We show for the first time that human foreskin keratinocytes can be infected by C. trachomatis and that serovars D and L2 form normal inclusions and robustly replicate in these cells suggesting that the human foreskin may be infected during early stages of colonization.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Moreover, dominant producers of interleukin-6 (IL-6) at sites of peripheral inflammation, fibroblasts are now recognized for their major contribution to inflammatory regulation ( 9 , 10 ). Fibroblasts are emerging with a key role in local innate immunity evoked during response to pathogens as well as vaccines ( 11 14 ).…”
Section: Introductionmentioning
confidence: 99%